Single‐cell RNA‐seq reveals distinct dynamic behavior of sex chromosomes during early human embryogenesis. Issue 7 (15th May 2019) - Zhou, Qing; Wang, Taifu; Leng, Lizhi; Zheng, Wei; Huang, Jinrong; Fang, Fang; Yang, Ling; Chen, Fang; Lin, Ge; Wang, Wen‐Jing; Kristiansen, Karsten
Abstract: Several animal and human studies have demonstrated that sex affects kinetics and metabolism during early embryo development. However, the mechanism governing these differences at the molecular level before the expression of the sex‐determining gene SRY is unknown. We performed a systematic profiling of gene expression comparing male and female embryos using available single‐cell RNA‐sequencing data of 1607 individual cells from 99 human preimplantation embryos, covering development stages from 4‐cell to late blastocyst. We observed consistent chromosome‐wide transcription of autosomes, whereas expression from sex chromosomes exhibits significant differences after embryonic genome activation (EGA). Activation of the Y chromosome is initiated by expression of two genes, RPS4Y1 and DDX3Y, whereas the X chromosome is widely activated, with both copies in females being activated after EGA. In contrast to the stable activation of the Y chromosome, expression of X‐linked genes in females declines at the late blastocyst stage, especially in trophectoderm cells, revealing a rapid process of dosage compensation. This dynamic behavior results in a dosage imbalance between male and female embryos, which influences genes involved in cell cycle, protein translation and metabolism. Our results reveal the dynamics of sex chromosomes expression and silencing during early embryogenesis. Studying sex differences during human embryogenesis, as well as understanding the process of X chromosome inactivation and their effects on the sex bias development of in vitro fertilized embryos, will expand the capabilities of assisted reproductive technology and possibly improve the treatment of infertility and enhance reproductive health. Abstract : Sex chromosomes show distinct expression pattern during early embryogenesis. Dynamic behavior of sex chromosomes leads to dosage imbalance of gene expression between sex. These genes may influence the development of in vitro fertilized embryos by regulating multiple biological processes.